Development of standardized nursing terminology for the process documentation of patients with chronic kidney disease - Pu, Shi; Peng, Hongmei; Li, Yang; Huang, Xia; Shi, Yu; Song, Caiping (Frontiers in Nutrition, 2024)
Introduction: European Nursing care Pathways (ENP) is a professional care language that utilizes software to map care processes and utilize the data for research purposes, process control, and personnel requirement calculations. However, there is a lack of internationally developed terminology systems and subset specifically designed for the nutritional management of CKD. The aim of this study was to create a subset of the standardized nursing terminology for nutrition management in patients with chronic kidney disease (CKD).: According to the guidelines for subset development, four research steps were carried out: (i) Translation of version 3.2 of the ENP (chapter on kidney diseases) and understanding of the framework structure and coding rules of the ENP; (ii) Identification of relevant six-dimensional nursing terms; (iii) Creation of a framework for the subset; (iv) Review and validation by experts.Results: A subset for CKD nutritional care was created as part of this project, comprising 630 terms, with 17 causal relationships related to nursing diagnoses, 115 symptoms, 31 causes, 34 goals/outcomes, 420 intervention specifications and 13 resources, including newly developed care terms. All terms within the subset have been created using a six-step maintenance procedure and a clinical standard pathway for nutrition management in the SAPIM mode.Implications for nursing practice: This terminology subset can facilitate standardized care reports in CKD nutrition management, which is used to standardize nursing practice, quantify nursing, services, guidance on care decisions, promoting the exchange and use of CKD nutrition data and serve as a reference for the creation of standardized subset of nursing terminology in China.